Osteoporosis in liver disease: pathogenesis and management. (June 2016) - Handzlik-Orlik, Gabriela; Holecki, Michał; Wilczyński, Krzysztof; Duława, Jan
Osteoporosis affects a substantial proportion of patients with chronic liver disease. Pathologic fracture in osteoporosis significantly affects quality of life and life expectancy. By some estimates, 40% of patients with chronic liver disease may experience osteoporotic fracture. In this study we review the pathogenesis, diagnosis and treatment of specific liver disease entities and their relation to osteoporosis.